REPLACING SODA ASH (NaOH) WITH KALIUM HYDROXYDE (KOH) IN DESTILATION OF BINARY ETHANOL-WATER MIXTURE - Istiqomah, Ana Ulfa; Rahmawati, Fitria; Nugrahaningtyas, Khoirina Dwi (ALCHEMY Jurnal Penelitian Kimia, 2016)
Soda ash (NaOH) has been used in bioethanol production in the second step destillation to increase the purity up to 90%. The destillation process will produce waste water with a high sodium content. The soda ash itself serve as an electrolyte to modify the colligative properties of the water-ethanol mixture allowing the disappearance of azeotropic point. This research aims to study the replacement of NaOH with KOH, in which the kalium is a nutrient to maintain soil fertility. This research study the thermodynamics properties, vapor-liquid equilibrium, colligative properties and also its azeotropic point in the destillation of water-ethanol mixture when KOH and NaOH were used as the additive. A model of water-ethanol mixture at a various composition of 0-100 weight % of ethanol was used. The electrolyte addition was 0.1 mol electrolyte/total weight of ethanol-water. The result shows that the addition of electrolyte into ethanol-water mixture eliminate the azeotropic point and allows the ethanol molecules to separate from water. The enthalpy of mixing between water-ethanol is 239.601 kJ/mol. It becomes 259.796 kJ/mol and 264.793 kJ/mol after the addition of NaOH and KOH, respectively. It confirming the endothermic mixing process due to different polarity between water and ethanol. The presence of electrolyte even reduce more their molecular interaction. However, the change to irregularity result a high positive entropy values that result the negative Gibbs free energy. It confirms the spontaneity of mixing. The vaporization enthalpy, Hvap, of water-ethanol mixture is 76.229 kJ/mol and it becomes 235.366 kJ/mol and 126.189 kJ/mol after the addition of NaOH and KOH. It indicates that the presence of electrolyte inhibites vaporization of water as the major component and allowing ethanol molecules to vapor producing more high purity ethanol.